\(P=\frac{1}{2000.1999}-\frac{1}{1999.1998}-...-\frac{1}{3.2}-\frac{1}{2.1}\)
\(\Rightarrow P=\frac{1}{2000.1999}-\left(\frac{1}{1.2}+\frac{1}{2.3}+...+\frac{1}{1998.1999}+\frac{1}{1999.2000}\right)\)
\(\Rightarrow P=\frac{1}{2000.1999}-\left(\frac{1}{1}-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+...+\frac{1}{1999}-\frac{1}{2000}\right)\)
\(\Rightarrow P=\frac{1}{1999.2000}-\left(1-\frac{1}{2000}\right)\)
\(\Rightarrow P=\frac{1}{1999}-\frac{1}{2000}-\frac{1999}{2000}\)
\(\Rightarrow P=\frac{1}{1999}-1\)
\(\Rightarrow P=\frac{-1998}{1999}\)
\(\Rightarrow P+\frac{1997}{1999}=\frac{-1}{1999}\)
Vậy...